Concerns Over Vuse e-Cigarette Digital Marketing and Implications for Public Health Regulation: Content Analysis - Eileen Han; Lauren K Lempert; Francesca Vescia; Bonnie Halpern-Felsher (JMIR Formative Research)
Abstract BackgroundElectronic cigarettes (e-cigarettes) are the most used form of tobacco products among adolescents and young adults, and Vuse is one of the most popular brands of e-cigarettes among US adolescents. In October 2021, Vuse Solo became the first e-cigarette brand to receive marketing granted orders (MGOs) from the US Food and Drug Administration (FDA), authorizing its marketing and their tobacco-flavored pods. Vuse Ciro and Vuse Vibe, and their tobacco-only (“original”) e-liquids, were authorized for marketing in May 2022 and Vuse Alto tobacco-flavored devices were authorized in July 2024. These marketing authorizations are contingent upon the company adhering to the MGOs’ stated marketing restrictions, including reducing exposure and appeal to youth via digital, radio, television, print, and point-of-sale advertising. ObjectiveIn this study, we analyzed the official social media channels of Vuse (Instagram and Facebook) to examine how Vuse marketed its products on social media and whether these marketing posts contain potentially youth-appealing themes. MethodsWe conducted content analysis of the official RJ Reynolds Vapor Company Instagram and Facebook accounts. We collected all posts from October 10, 2019, when RJ Reynolds Vapor Company submitted its premarket tobacco product application to the FDA, to February 21, 2022, to cover the first winter holiday season after the MGO. Two coders developed the codebook with 17 themes based on the Content Appealing to Youth index to capture the posts’ characteristics and potentially youth-appealing content. We calculated the percentage of posts in which each code was present. ResultsA total of 439 unique posts were identified. During this study’s period, there were no posts on Instagram or Facebook marketing Vuse Solo (the authorized product at that time). Instead, Vuse Alto (unauthorized to date of study) was heavily marketed, with 59.5% (n=261) of the posts specifically mentioning the product name. Further, “Vuse” more generally was marketed on social media without differentiating between the authorized and unauthorized products (n=182, 41.5%). The marketing messages contained several potentially youth-appealing themes including creativity or innovation (n=189, 43.1%), individuality or freedom (n=106, 24.2%), and themes related to art (n=150, 34.2%), music (n=77, 17.5%), sports (n=125, 28.5%), nature (with n=49, 11.2% of the posts containing flora imageries), alcohol imagery (n=10, 2.3%), and technology (n=6, 1.4%). ConclusionsAlthough Vuse Alto e-cigarettes had not yet obtained FDA marketing authorization during the 28 months of data collection, they were the primary Vuse e-cigarette devices marketed on social media. Vuse social media posts use themes that are appealing to and likely promote youth use, including creativity and innovation, individuality or freedom, arts and music, nature, technology, and alcohol imagery. The FDA should (1) prohibit companies from comarketing unauthorized products alongside authorized products, and (2) exercise enforcement against even authorized products that are marketed using youth-appealing features.